MODULAR RESEARCH EQUIPMENT FOR ON-LINE INSPECTION IN ADVANCED MANUFACTURING SYSTEMS - Davrajh, S; Bright, G; Stopforth, R (The South African Journal of Industrial Engineering, 2012)
The significance of inspection processes increases when producing parts with high levels of customer input. These processes must adapt to variations in significant product characteristics. Mass customisation and reconfigurable manufacturing are currently being researched as ways to respond to high levels of customer input. This paper presents the research and development of modular inspection equipment that was designed to meet the on-line quality requirements of mass customisation and reconfigurable manufacturing environments. Simulated results were analysed for application in an industrial environment. The implementation of the equipment in South Africa is briefly discussed. The research indicates that manufacturers need only invest in the required equipment configurations when they are needed for on-line inspection.